Dynamics of high-latitude pathches and associated small-scale irregularities during the October and November 2003 storms - De Franceschi, G.; Alfonsi, Lu.; Romano, V.; Aquino, M.; Dodson, A.; Mitchell, C. N.; Spencer, P.; Wernik, A. W. (Journal of Atmospheric and Solar-Terrestrial Physics, 2008)
Observations from a network of specially equipped GPS scintillation receivers in Northern Europe are used to investigate the dynamics of ionospheric plasma during the storm events of 30 October and 20 November 2003. The total electron content (TEC) and scintillation data, combined with ionospheric tomography produced by the multi-instrument data analysis system (MIDAS), reveal strong enhancements and steep gradients in TEC during nighttime under a prevailing negative Bz component of the interplanetary magnetic field (IMF). Amplitude and phase scintillation maxima are often co-located with the TEC gradients at the edge of plasma patches, revealing the presence of small-scale irregularities and suggesting association with a tongue of ionization (TOI) convecting in an anti-sunward direction from the American sector across the polar cap. Similarities and differences between the ionospheric response to the two storms are investigated. The 30 October event reveals a quite complex scenario showing two phases of plasma dynamics: the former reflects the expected convection pattern for IMF Bz southward and the latter possibly indicates a sort of TEC plasma stagnation signature of the more complex convection patterns during several positive/negative excursions of IMF Bz. Published 879-888 3.9. Fisica della magnetosfera, ionosfera e meteorologia spaziale JCR Journal reserved